2022
DOI: 10.3390/ijms23052727
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Assessment of the Vela Diagnostics NGS Assay for HIV Genotyping and Resistance Testing: The Apulian Experience

Abstract: Drug-resistance monitoring is one of the hardest challenges in HIV management. Next-generation sequencing (NGS) technologies speed up the detection of drug resistance, allowing the adjustment of antiretroviral therapy and enhancing the quality of life of people living with HIV. Recently, the NGS Sentosa® SQ HIV Genotyping Assay (Vela Diagnostics) received approval for in vitro diagnostics use. This work is the first Italian evaluation of the performance of the Vela Diagnostics NGS platform, assessed with 420 H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 37 publications
1
0
0
Order By: Relevance
“…In conclusion, our study complements previous studies [ 23 , 24 , 33 , 46 , 47 , 48 , 49 ] that support the notion that the population sequencing and high-throughput sequencing are well correlated. Moreover, using HTS-GRT, we can detect minority DRMs that have previously been reported to be associated with poor virologic suppression.…”
Section: Discussionsupporting
confidence: 89%
“…In conclusion, our study complements previous studies [ 23 , 24 , 33 , 46 , 47 , 48 , 49 ] that support the notion that the population sequencing and high-throughput sequencing are well correlated. Moreover, using HTS-GRT, we can detect minority DRMs that have previously been reported to be associated with poor virologic suppression.…”
Section: Discussionsupporting
confidence: 89%
“…A recent Italian study that evaluated the Vela Diagnostics system showed better results with this NGS technology, compared to Sanger sequencing, in terms of the success rate, accuracy, repeatability, and reproducibility of results [21]. Several other studies conducted prior to this Italian study had evaluated and demonstrated the performance of the Vela Dx Sentosa next-generation sequencing system for HIV-1 cDNA genotypic resistance [22][23][24][25].…”
Section: Introductionmentioning
confidence: 85%
“…A recent Italian study that evaluated the Vela Diagnostics system showed better results with this NGS technology, compared to Sanger sequencing, in terms of success rate, accuracy, repeatability, and reproducibility of results [12]. In the present study, for the first time, we used a Vela Sentosa kit to sequence HIV genomes using the Illumina Miseq platform.…”
Section: Introductionmentioning
confidence: 87%